Numeracy Skills of Junior High School Students: A Comparative Study Based on Learning Approach Interventions - Ana Paula Tae; Aloisius Loka Son; Yohanes Jefrianus Kehi; Camilo Andrés Rodríguez-Nieto; Javier García-García (CV. Samuel Manurung and Co, 2025)
This study aims to determine the achievement and improvement of students' numeracy skills based on the Realistic Mathematics Education (RME) approach intervention. This research used a quasi-experimental method with a pretest-posttest control group design. The research sample consisted of two classes, namely the experimental class that used the RME approach and the control class that used conventional methods. The instrument used was a numeracy description test question on the material of the Two-Variable Linear Equation System. The results showed that the achievement and improvement of students' numeracy skills, who learned through the realistic mathematics education approach, were better than students who learn through conventional approaches. This shows that learning with a realistic mathematics education approach can facilitate the numeracy skills of junior high school students. It is hoped that future researchers can apply the realistic mathematics education approach to other mathematical skills.